1991
DOI: 10.1164/ajrccm/144.5.1102
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Smoking on Mechanical Properties of the Lungs in Idiopathic Pulmonary Fibrosis and Sarcoidosis

Abstract: Interstitial lung disease is characterized by interstitial inflammatory cell infiltration and fibrosis, a reduction in lung volumes, an increase in lung elastic recoil, and rapid shallow respirations. However, the alterations in lung volumes and elastic recoil as well as in breathing pattern are extremely variable, and the values are normal in a number of patients. In order to determine whether the effects of smoking could account for the variability in lung volumes and breathing pattern, we evaluated the elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 10 publications
4
19
0
3
Order By: Relevance
“…Our data support the conclusions of Saag et al, who demon- strated that smoking was the most consistent independent predictor of radiographic and physiologic abnormalities suggestive of interstitial lung disease in RA [9]. A similar correlation between tobacco exposure and disease has been observed in patients with eosinophilic granuloma [39,40], usual interstitial pneumonitis [41] and sarcoidosis [40,41]. Smoking in itself has been convincingly shown to be associated with AHR in patients who have mild to moderate COPD.…”
Section: Discussionsupporting
confidence: 91%
“…Our data support the conclusions of Saag et al, who demon- strated that smoking was the most consistent independent predictor of radiographic and physiologic abnormalities suggestive of interstitial lung disease in RA [9]. A similar correlation between tobacco exposure and disease has been observed in patients with eosinophilic granuloma [39,40], usual interstitial pneumonitis [41] and sarcoidosis [40,41]. Smoking in itself has been convincingly shown to be associated with AHR in patients who have mild to moderate COPD.…”
Section: Discussionsupporting
confidence: 91%
“…Lung volumes may be relatively preserved in smokers with IPF due to coexisting emphysema, with the FEV 1 /FVC ratio remaining normal 35 36 104 – 106. In systemic sclerosis, an isolated reduction in T lco may indicate pulmonary vascular disease, especially when T lco levels are markedly reduced (discussed more fully in Section 21).…”
Section: Lung Function Testing In Ildmentioning
confidence: 99%
“…Hanley et al [7] reported that, 75.0% cases of IPF had a history of smoking, which was associated with acceleration of disease process. On PFT, a restrictive ventilatory defect is the most frequent finding in patients of DPLD, especially in IPF [8].…”
Section: Discussionmentioning
confidence: 99%